Bacteria in the milk of sheep with or without mastitis- mini Review - Tonamo, Andualem; Komlósi, István; Peles, Ferenc (Acta Agraria Debreceniensis, 2019)
From a nutritional point of view, sheep milk is more valuable than cow and goat milk and the interest for sheep milk is increasing in many countries. However, sheep milk is easily contaminated during milking, handling, and transport and it is an ideal medium for bacterial propagation. Consequently, sheep milk spoils quite quickly. The proper, clean handling of milk is not only of sanitarian interest, but it also serves the farmers’ interests, because contaminated milk may not be distributed, and is unsuitable for producing good quality products. Following this technological trend, this review addresses the bacterial composition of sheep milk with and without mastitis. Even though sheep milk contains a lot of bacteria, this review article highlighted total plate count, Enterobacteriaceae, coliform, Staphylococcus aureus, Escherichia coli, Listeria monocytogenes, Campylobacter, Salmonella spp. and Streptococcus spp. Mastitis in sheep is a vital cause of mortality, reduction in milk production and early culling. The reported risk factors for mastitis in sheep were age, a case of mastitis, breed, husbandry systems, and location. The main priority should be implementation of programs to minimize human pathogenic bacteria and mastitis in raw ewe milk.